Tourism Sector, Economic Growth, and Poverty: A Simultaneous Analysis in Indonesia - Neli Agustina; Linierti Ajeng Aulia Putri (Journal of Developing Economies, 2026)
Objective: The tourism sector is a significant component of Indonesia’s economic framework. This study aims to analyze the contribution of the tourism sector to the growth of Gross Regional Domestic Product (GRDP) and poverty reduction. Design/Methods/Approach: This study used secondary panel data from Statistics Indonesia (BPS) covering 34 provinces in Indonesia over the 2018-2022 period. A Simultaneous-equation model estimated using two-stage least squares (2SLS) is applied to examine the endogenous relationship among the tourism sector, Gross Regional Domestic Product (GRDP), and poverty. The selected exogenous variables consist of the hotel room occupancy rate, the number of tourist attractions, food and beverage providers, motorized vehicles, the realization of investment, the information and communication technology development index, unemployment rate, life expectancy, average years of schooling, and the consumer price index. Findings: The results show a simultaneous relationship between domestic tourist expenditure, GRDP, and poverty in Indonesia for 2018-2022. Increasing tourist expenditure raises GRDP, increasing GRDP reduces poverty, and lower poverty in turn boosts GRDP and domestic tourist expenditure. Originality/Value: Previous studies largely view the relationships between the tourism sector and GDP, and between GDP and poverty, as one-way. Different from these approaches, this study starts from the theoretical framework of Tourism-Led Economic Growth (TLG), Economic-Driven Tourism Growth (EDTG), and the concept of the vicious circle of poverty. Based on these theories, this study proposes that the two pairs of variables influence one another. Thus, tourism and GDP, as well as GDP and poverty, can influence each other reciprocally rather than in one direction. Practical/Policy implication: Tourism development, economic growth, and poverty alleviation need to be planned in an integrated manner. Implementing policies that encourage investment in the tourism sector and ensure a more equitable distribution of economic benefits can strengthen a sustainable, mutually beneficial cycle among these three sectors.